افضل الممارسات لادارة وثائق الجهات الحکومیة على شبکات التواصل الاجتماعى - د. أمانى محمد عبد العزیز (المجلة الدولية لعلوم المكتبات والمعلومات)
Most governments around the world tend to introduce e-government, thatis, the use of internet technology as a platform for exchanging information,providing services and transacting with citizens, businesses, and otherStakeholders of government. The keenness to provide governmental services ina smooth and efficient manner to citizens has prodded governments around theglobe into introducing technologies, notably among which is the socialnetworking.This research paper attempts to investigate how to manage governmentrecords on social networking, and how to meet the challenges posed by it toensure optimal performance and level of services on the national andinternational levels as well as the active participation of subscribers in policy anddecision making. The fact that the social networking is subject to change andconstant upgrading has cast its shadows on the records available on its pages.Hence, the need arises to manage such records in a different, systematicmanner.To meet this need, a lot of countries around the world have issuedguidelines on how to deal with records available on social networking. The paperat hand attempts to examine such Best practices, in a bid to follow them in theArab world.